Reconfigurable microstrip antennas integrated with truncated rhombus-like slotted patch structure / Suzilawati Muhamud @ Kayat - Muhamud @ Kayat, Suzilawati (2015)
Reconfigurable microstrip antennas have so many attractive features to offer such as the ability to reconfigure independently in order to perform entirely different functions for numerous applications. They can provide diversity functions to mobile communications in three main categories: operating frequency, radiation pattern and polarization. This is in contrast with the conventional antennas which normally offer one particular function at a time in a single antenna. There are many types of reconfigurable antennas that have been demonstrated in previous researches with regards to these three different categories. In this research, the development of reconfigurable antennas can be divided into two main categories, which are based on operating frequency and radiation pattern. Prior to that, two novel structures of aperture coupled microstrip antennas in a single configuration at two different frequencies have been developed, which are denoted as TRSPA-1 and TRSPA-2. Each antenna employs a truncated rhombus-like patch shape embedded with a unique 'zig-zag' patch slots. The introduction of different orientations of slot embedded on the radiating patch has resulted in two different operating frequencies. Each antenna has the same patch size although two different frequencies are achieved due to the fact that the size of the patch slot and its orientations in x- and y-axis give significant effects on the excitations of the resonant frequency. Based on the combination of these two designs, a frequency reconfigurable microstrip antenna was developed in two-element array configuration, denoted as FRTRSPA-1. To further enhance the characteristics, the antenna elements of FRTRSPA-1 have been extended to four elements in a planar or corporate feed configuration, which is known as FRTRSPA-2 …